A rapid administration of GW4064 inhibits the NLRP3 inflammasome activation independent of farnesoid X receptor agonism. Issue 18 (20th August 2017) - Xie, Shujun; Guo, Chuansheng; Chi, Zhexu; Huang, Bo; Wu, Yihua; Wang, Di; Xia, Dajing
Abstract : GW4064 is a small molecule known to be an agonist of the nuclear farnesoid X receptor (FXR). We found that GW4064 inhibits the NLR family CARD domain containing 3 (NLRP3) inflammasome activation in an FXR‐independent manner as evidenced by its similar inhibitory effect on NLRP3 inflammasome activation in FXR‐deficient macrophages. Interestingly, GW4064 decreases the nigericin‐induced oligomerization and ubiquitination of ASC which is critical for the NLRP3 inflammasome activation. In vivo results indicate that GW4064 could partially rescue the symptoms of NLRP3‐dependent inflammatory disease models. These results not only necessitate cautious interpretation of the biological function of GW4064 as an FXR agonist, but also provide a potential therapeutic approach using GW4064 in the treatment of NLRP3‐related diseases. Abstract :